A decolonial approach to a socially just curriculum? a case study of a first-year common course in an emerging post-apartheid University eMzansi Afrika - Mona, Msakha (School of Education, 2026)
This qualitative case study sought to explore whether and how the University of Mpumalanga (UMP) imagined social justice in its first-year common course, MIC100 (Mpumalanga in Context). The UMP is one of the only two universities established after apartheid in South Africa, and it does not have a colonial and apartheid history. However, its newness does not absolve the UMP from coloniality, thus the study found that the institution is implicated in coloniality due to its existence within a higher education environment that is pervasively Eurocentric. Thus, the study explored how the UMP worked with this complication through its curriculum in MIC100. Theories of social justice and decoloniality framed the study. While pointing out some of UMP's complicities in coloniality, the study found MIC100 to have made significant moves towards social justice and decolonization. The main data for this research was the students' reviews of MIC100, student interviews, and the UMP's documentary data which were analyzed on NVivo. Among the implications of the study, is the need and call for universities to be more intentional in responding to the decolonial question in ways that achieve social justice. Therefore, the findings reveal some of the strategies that were employed in MIC100 that can be adapted by educational institutions, lecturers, and curriculum designers. The strategies include efforts to recognize black students and their cultural products such as African languages; and creating teaching and learning environments where students can feel ayoba.